Roles of Microwave Oven in Preparing Microbiological Growth Media - Prijana, Christian; Mulyana, Yanti; Hidayat, Basuki (Althea Medical Journal, 2016)
Background: Sterilization of a growth medium before being utilized is a very important step in a microbiology laboratory. The common method for this purpose is by using the autoclave. However, autoclaving takes more time. To overcome this limitation, we tried to use the microwave oven. The aim of this study was to evaluate the ability of microwave oven in preparing the growth media.Methods: This was a laboratory experimental study conducted at Microbiology Laboratory, Faculty of Medicine, Universitas Padjadjaran, from October to November 2014. The growth media used were: MacConkey agar, in petri dishes, inoculated with Escherichia coli; Sabouraud agar, in petri dishes, inoculated with Candida albicans; Kligler iron agar (KIA), in reaction tubes, inoculated with Escherichia coli and Salmonella Typhi; Simmons citrate agar, in reaction tubes, inoculated with Klebsiella pneumoniae; Mueller-Hinton (M-H) broth, in reaction tubes, inoculated with Escherichia coli; and Motility Indole Urea (MIU) semisolid agar, in reaction tubes, inoculated with Proteus sp.The media would be heated by microwave for 1, 2, and 3 minutes. Results: From the total 54 dishes/tubes of various microwave-sterilized media, contaminations were only seen at 5 dishes/tubes. Most of the media, except the one-minute-heated Mueller-Hinton broth, were sterilized more than half dishes/tubes. The identification function of all media in this study was performed well. Conclusions: The utilization of microwave oven as an alternative sterilizing apparatus for microbiological growth media is very potential, particularly for two and three minutes duration of heating. [AMJ.2016;3(1):1â5]DOI:Â 10.15850/amj.v3n1.469